Age-related impairment in Addenbrooke's cognitive examination revised scores in patients with amyotrophic lateral sclerosis. Issue 7 (2nd October 2018) - Masuda, Michihito; Watanabe, Hirohisa; Tanaka, Yasuhiro; Ohdake, Reiko; Ogura, Aya; Yokoi, Takamasa; Imai, Kazunori; Kawabata, Kazuya; Riku, Yuichi; Hara, Kazuhiro; Nakamura, Ryoichi; Atsuta, Naoki; et al.
Abstract: Objective: Older age is thought to be a risk factor for cognitive impairment in amyotrophic lateral sclerosis (ALS). However, very few clinical studies have investigated this relationship using sufficient numbers of healthy controls that correspond to each generation. The purpose of this study was to determine the age-related changes of Addenbrooke's Cognitive Examination-Revised (ACE-R) score in ALS patients by comparing healthy controls of various ages. Methods: 131 ALS patients (86 males, 45 females; mean age: 64.8 ± 10.2; mean education: 12.5 ± 2.7) and 151 age-, gender-, and education-matched healthy controls were enrolled. We applied ACE-R, which could evaluate not only global cognition but five cognitive subdomains that included orientation/attention, memory, verbal fluency, language, and visuospatial ability. Results: ALS patients had significantly lower total and subdomain scores of ACE-R than healthy controls. Multiple regression analysis suggested that age at examination and age at onset had significant influence on ACE-R scores. When we divided ALS patients and healthy controls into 4 groups according to age at examination for ALS, total and each subdomain scores were significantly lower with age, particularly in the older-middle and the oldest group (66.31 years or more) of ALS compared with healthy controls. Locally weighted scatterplot smoothing analysis supported that these reductions of ACE-R total and subdomain scores in ALS patients were more accelerated by approximately 60 years as compared with healthy controls. Conclusion: ALS patients showed accelerated age-related ACE-R score reduction beyond normal ageing processes.